2007
DOI: 10.1080/08920750601169659
|View full text |Cite
|
Sign up to set email alerts
|

Facts, Fictions, and Failures of Integrated Coastal Zone Management in Europe

Abstract: Nearly 40 years on since its first tentative steps in North America, this article considers whether Integrated Zone Coastal Management (ICZM) in Europe has grown to maturity as a form of governance. The article summarizes the findings of recent research concerning the levels of implementation of coastal management in Europe, with particular reference to the UK experience. A research framework is used to identify the different motivations behind the social actor groups involved in coastal management. The appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(84 citation statements)
references
References 35 publications
0
76
0
8
Order By: Relevance
“…There is already great variation among countries subjected to the same or similar international directives. As an example, the Netherlands national "stocktake" has concluded that no new system for ICZM is needed but that it will form part of a national spatial planning strategy (Shipman and Stojanovic, 2007). At the same time, the French stocktake highlights the importance of intensifying the implementation of ICZM at the local level, including local capacity building, and the establishment of a national council for implementing ICZM (Shipman and Stojanovic, 2007).…”
Section: A Framework For Evaluation Based On Past Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is already great variation among countries subjected to the same or similar international directives. As an example, the Netherlands national "stocktake" has concluded that no new system for ICZM is needed but that it will form part of a national spatial planning strategy (Shipman and Stojanovic, 2007). At the same time, the French stocktake highlights the importance of intensifying the implementation of ICZM at the local level, including local capacity building, and the establishment of a national council for implementing ICZM (Shipman and Stojanovic, 2007).…”
Section: A Framework For Evaluation Based On Past Studiesmentioning
confidence: 99%
“…As an example, the Netherlands national "stocktake" has concluded that no new system for ICZM is needed but that it will form part of a national spatial planning strategy (Shipman and Stojanovic, 2007). At the same time, the French stocktake highlights the importance of intensifying the implementation of ICZM at the local level, including local capacity building, and the establishment of a national council for implementing ICZM (Shipman and Stojanovic, 2007). We therefore conduct a qualitative comparative study of progress in ICZM focusing on integration achieved by the same mechanisms of ICZM implemented by different countries.…”
Section: A Framework For Evaluation Based On Past Studiesmentioning
confidence: 99%
“…Actually, we live in a strange impasse because the efforts at research, planning and policy in ICZM achievement remain disjointed without any temporal and territorial consistency. The main obstacles, already envisaged for other Mediterranean countries (Shipman and Stojanovic 2007), to an effective ICZM implementation in Italy, are:…”
Section: The Italian Gapmentioning
confidence: 99%
“…The various European Union (EU) policies and directives emerged as complementary instruments, the most important being (Borja 2006, Ducrotoy & Elliott 2006, Borja et al 2010 Table 1 shows a brief sample of the programmes adopted within the EU at 3 scales: (1) legislation and policies applied at the EU level, (2) programmes to be implemented at transnational level for joint management of European seas (not exclusively within EU member states), and (3) legislation mainly developed at the national level, not necessarily to address EU programmes. The individual EU member states have different approaches to coastal management with a variety of coastal management initiatives and legislations (Gibson 2003, Shipman & Stojanovic 2007. In Spain, for instance, complementary to the Coastal Law, several autonomous communities have specific regional programmes of action (Sardá et al 2005).…”
Section: Integrated Coastal Zone Managementmentioning
confidence: 99%
“…Hershman et al (1999) and Humphrey et al (2000) described the key features for its success and its shortcomings. Coastal management programmes on a European scale are more recent (Humphrey et al 2000, Shipman & Stojanovic 2007. The various European Union (EU) policies and directives emerged as complementary instruments, the most important being (Borja 2006, Ducrotoy & Elliott 2006, Borja et al 2010 Table 1 shows a brief sample of the programmes adopted within the EU at 3 scales: (1) legislation and policies applied at the EU level, (2) programmes to be implemented at transnational level for joint management of European seas (not exclusively within EU member states), and (3) legislation mainly developed at the national level, not necessarily to address EU programmes.…”
Section: Integrated Coastal Zone Managementmentioning
confidence: 99%